Power system transient stability improvement via thyristor-controlled series compensation and static phase shifter - Jiang, Fan (2010)
Full utilization of transmission capability of long lines is often limited by transient stability consideration. Techniques based on the concept of Flexible AC Transmission System (FACTS) are being explored to overcome this constraint. Design and control aspects of two different kinds of FACTS devices in this study for the improvement of transient stability of power systems are investigated. The purpose of utilizing these devices is to achieve fast and precise control of power flow through a transmission line. Thyristor-Controlled Series Compensation (TCSC) controls the power flow by varying the effective line impedance, while the Static Phase Shifter (SPS) achieves the same aim by adjusting the phase angle difference between the sending- and receiving-end voltages of the line. These devices, with appropriate control schemes, are used to enhance the stability of a power system by suppressing the power oscillations and by providing additional damping to the network.